Scaffolding dalam menyelesaikan masalah Matematis berdasarkan kecerdasan sosial Siswa SMP Kabupaten Gowa - Ahmad Talib; Ilham Minggi (Seminar Nasional LP2M UNM, 2019)
This research is a qualitative research with descriptive method. This study aimed to describe the provision of Scaffolding in solving mathematical problems in the two-variable linear equations system (SPLDV) material by involving students' social intelligence rankings. It was also to see the provision of Scaffolding in solving SPLDV mathematical problems. The subjects of this study were students of class VIII-J of SMP Negeri 1 Sungguminasa Gowa, the even semester of the school year 2017/2018, that was one student with top-ranked social intelligence. The instrument used in this study was the mathematical problem-solving test, aimed to collect written data about students' mistakes in solving SPLDV mathematical problems. This problem material consisted of one questions formulated in the form of math word problem. The next instrument used was the social intelligence questionnaire. This questionnaire is in the form of a Likert Scale, this questionnaire consisted of 27 items, this instrument was given to identify the stages of students’ social intelligence, and another instrument was the interview guide. The results of this study showed that the mathematical problem-solving of SPLDV is quite helpful for students, even though at first the students still seemed low in absorbing Scaffolding steps to solve the problem. After giving some reinforcement, subjects can follow the Scaffolding steps even though not maximally. The results of the interview also indicate that giving Scaffolding in solving mathematical problems based on social intelligence showed the students’ ability who are relatively standart (medium) in solving SPLDV mathematical problems. The role of the teacher in giving Scaffolding is very important, where the teacher can assist students in completing tasks or concepts that are not initially able to be obtained independently, so that in solving mathematical problems, teachers need to pay attention to the suitability of each level of Scaffolding in solving SPLDV mathematical problems. Because each level of Scaffolding given and in accordance with the needs of students in the learning process, this can help students in solving mathematical problems.